PPARs as Key Mediators in the Regulation of Metabolism and Inflammation - Manuel Vázquez-Carrera (International Journal of Molecular Sciences, 2022)
Nuclear receptors (NRs) form a large family of ligand-dependent transcription factors that control the expression of a multitude of genes involved in diverse, vital biological processes [...]